PENGARUH VARIAN MENU DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN WIZZMIE SURABAYA - Pramesstya, Ditta; Rafida, Veni (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This study aims to analyze the effect of menu variety on Wizzmie Surabaya customer loyalty and analyze the influence of service quality on Wizzmie Surabaya customer loyalty. This study uses the variables of menu variety, service quality, and customer loyalty with a causal quantitative approach. The population in this study is the Millennial and Z generation in the city of Surabaya who have bought at Wizzmie Surabaya. The sampling technique in this study is purposive sampling which uses the Hair formula with a total of 150 respondents. The data collection technique uses an online questionnaire through google forms. The researcher used the Structural Equation Modelling Partial Least Squares (SEM-PLS) data analysis technique with the SmartPLS 3.0 tool. The testing model in this study includes outer model test, inner model and hypothesis testing. The results of this study prove that: (1) menu variety affects customer loyalty of Wizzmie Surabaya, (2) service quality affects customer loyalty of Wizzmie Surabaya. (3) menu variety and service quality simultaneously affect Wizzmie Surabaya's customer loyalty.